Componeer as an aesthetic treatment option for anterior teeth: a case report - Irmaleny Irmaleny; Opik Taofik Hidayat; Raden Ajeng Pritasya Handayani (BMC, 2024)
Abstract Introduction Structural abnormalities or anomalies in the anterior teeth, also known as the aesthetic zone, are an important problem for patients and a challenge for dentists. Structural abnormalities or tooth anomalies can change in color, shape, and function. Most dentists prefer minimally invasive aesthetic treatment. One of the aesthetic treatment options for anterior teeth is veneers. Veneer is a restoration that covers the labial part of the tooth with a thin layer of material to correct abnormalities in the color, shape, or function of the tooth. Veneer restoration can be done indirectly with porcelain material made in a laboratory and directly with composite material on the tooth surface or prefabricated which is available from the factory. Componeer is a prefabricated composite veneer that combines the aesthetic properties of ceramic veneers and the adhesive ability of composite veneers to the tooth structure. This case report describes the treatment of two central incisors that had been filled with composite and peg shapes on both lateral incisors using a componeer. Case report A 32-year-old female patient came to the Dental Conservation Clinic at Dentistry Hospital, Padjadjaran University with the main complaint of her right and left upper front teeth and wanted to repair her old fillings and close the gap between her right and left upper front teeth and her canine teeth. Clinical examination showed that teeth 11 and 21 had been filled with composite which had changed color and had an inharmonious shape as well as a gap between the upper front teeth on the right and left sides and the right and left canine teeth. Treatment The maxilla and mandibular teeth are molded for study models and working models. In the working model, a wax-up is carried out, then a mock-up on the patient's teeth. Next, choose the color and size of the components that match the mock up results. Teeth 11 and 21 had their old composite fillings cleaned and refilled with dentin colored composite, teeth 13, 12, 11, 21, 22, and 23 were prepared with a minimum thickness of 0.3 mm to make room for the componeer material. The teeth was etched and bonded, and bonding was applied to the inner surface of the componeer. The composite is placed on the inner surface of the componeer then placed on the labial surface of the tooth and pressed with a special tool, then light cured. The final step is polishing. Treatment results Teeth 13, 12, 11, 21, 22, and 23 which had undergone veneer treatment using componeer, were controlled after 1 week of treatment. The patient did not complain about the results of the treatment and said he was satisfied with the treatment.